2013
DOI: 10.1089/ten.tec.2012.0489
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Alternative to Cryopreservation for the Short-Term Storage of Stem Cells for Use in Cell Therapy Using Alginate Encapsulation

Abstract: Efficient transport of stem/progenitor cells without affecting their survival and function is a key factor in any practical cell-based therapy. However, the current approach using liquid nitrogen for the transfer of stem cells requires a short delivery time window is technically challenging and financially expensive. The present study aims to use semipermeable alginate hydrogels (crosslinked by strontium) to encapsulate, store, and release stem cells, to replace the conventional cryopreservation method for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 50 publications
0
66
0
Order By: Relevance
“…Cell pausing is clearly becoming accepted as a potential technology to preserve and transport mammalian cells. The research by Chen et al (2013) in particular, proves that the process of cell pausing can be successfully applied to stem cells, which holds great potential for its application to future cell therapies.…”
Section: Custodial and Most Recently Hypothermosol-frs (Hts-frs) (2-8mentioning
confidence: 95%
See 2 more Smart Citations
“…Cell pausing is clearly becoming accepted as a potential technology to preserve and transport mammalian cells. The research by Chen et al (2013) in particular, proves that the process of cell pausing can be successfully applied to stem cells, which holds great potential for its application to future cell therapies.…”
Section: Custodial and Most Recently Hypothermosol-frs (Hts-frs) (2-8mentioning
confidence: 95%
“…A current success in cell pausing under ambient conditions used human mesenchymal stromal cells (hMSC) and mouse embryonic stem cells (mESC) entrapped in a semi-permeable alginate hydrogel (Chen et al 2013). …”
Section: Custodial and Most Recently Hypothermosol-frs (Hts-frs) (2-8mentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike cryopreservation and, to a lesser extent, chilled preservation, the research with ambient temperature preservation is not as extensive and has only become an area of interest in light of the potential advantages this preservation method confers over the aforementioned preservation techniques. The potential of this technique is demonstrated by Chen et al (2013) who demonstrated that they were able to store hMSCs and mouse ESCs (mESCs) inside alginate hydrogels for 5 days in ambient conditions in an air-tight environment. Cell viability post-preservation was found to be 80% and 74% for the hMSCs and mESCs respectively [47].…”
Section: Hypothermic Storagementioning
confidence: 99%
“…The potential of this technique is demonstrated by Chen et al (2013) who demonstrated that they were able to store hMSCs and mouse ESCs (mESCs) inside alginate hydrogels for 5 days in ambient conditions in an air-tight environment. Cell viability post-preservation was found to be 80% and 74% for the hMSCs and mESCs respectively [47]. Similarly, Swioklo et al (2016) showed human adipose-derived stem cells could be encapsulated and stored at a range of temperatures, from 4-23C, although 15C was found to be the optimal [48].…”
Section: Hypothermic Storagementioning
confidence: 99%